2006
DOI: 10.1124/jpet.106.111245
|View full text |Cite
|
Sign up to set email alerts
|

Transport, Metabolism, and in Vivo Population Pharmacokinetics of the Chloro Benztropine Analogs, a Class of Compounds Extensively Evaluated in Animal Models of Drug Abuse

Abstract: Recently, extensive behavioral research has been conducted on the benztropine (BZT) analogs with the goal of developing successful therapeutics for cocaine abuse. The present study was conducted to characterize the contribution of dispositional factors in mediating the behavioral differences among the chloro BZT analogs and to identify cytochrome P450 enzymes involved in their metabolism. Bidirectional transport and efflux studies of four of the chloro BZT analogs were conducted. Screening with a panel of huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
26
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 29 publications
6
26
0
Order By: Relevance
“…Consequently, the residual error was fixed to 10.7% based on a sensitivity analysis, and the final selected value was the value resulting in the lowest objective function and the highest precision in estimation of interanimal variability. The 10.7% residual random error was comparable with the estimated or fixed values for previously studied BZT analogs using identical experimental technique (Othman et al, 2007). Figure 3 represents the relevant diagnostic plots for the final population pharmacokinetic model for 3Ј-Cl BZT, and it indicates that the model described the pharmacokinetics of 3Ј-Cl BZT without any systematic bias.…”
Section: Resultssupporting
confidence: 62%
See 3 more Smart Citations
“…Consequently, the residual error was fixed to 10.7% based on a sensitivity analysis, and the final selected value was the value resulting in the lowest objective function and the highest precision in estimation of interanimal variability. The 10.7% residual random error was comparable with the estimated or fixed values for previously studied BZT analogs using identical experimental technique (Othman et al, 2007). Figure 3 represents the relevant diagnostic plots for the final population pharmacokinetic model for 3Ј-Cl BZT, and it indicates that the model described the pharmacokinetics of 3Ј-Cl BZT without any systematic bias.…”
Section: Resultssupporting
confidence: 62%
“…The binding model was regressed to the microdialysis data from the two dose levels tested for each drug (data from 10 animals for 3Ј-Cl BZT and 12 animals for 4Ј,4Љ-diCl BZT). Because the plasma concentrations of the BZT analogs were not measured in the same animals in which the microdialysis experiments were conducted, the mean population pharmacokinetic parameters determined in the current study for 3Ј-Cl BZT and in a previous study for 4Ј,4Љ-diCl BZT (Othman et al, 2007) were used to simulate the plasma concentrations for a typical animal at the times of measurement of DA for each dose tested. The plasma concentrations for all the animals were then fixed to these typical values, and they were used as input for the pharmacodynamic modeling.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pharmacokinetic studies have found BZT analogs in brain shortly after injection, with only small differences in central nervous system permeability compared with cocaine (Raje et al, 2003;Othman et al, 2007). Despite this rapid central nervous system availability, Tanda et al (2005) showed slower increases in extracellular dopamine produced by 4-Cl-BZT compared with cocaine.…”
Section: Discussionmentioning
confidence: 99%